Tax Administration and Firm Performance : New Data and Evidence for Emerging Market and Developing Economies - Dabla-Norris, Era (IMF Working Papers; Working Paper ;, 2017)
Tax compliance costs tend to be disproportionately higher for small and young businesses. This paper examines how the quality of tax administration affects firm performance for a large sample of firms in emerging market and developing economies. We construct a novel, internationally comparable, and multidimensional index of tax administration quality (the TAQI) using information from the Tax Administration Diagnostic Assessment Tool. We show that better tax administration attenuates the productivity gap of small and young firms relative to larger and older firms, a result that is robust to controlling for other aspects of tax policy and of economic governance, alternative definitions of small and young firms, and measures of the quality of tax administration. From a policy perspective, we provide evidence that countries can reap growth and productivity dividends from improvements in tax administration that lower compliance costs faced by firms.